2014
DOI: 10.4097/kjae.2014.66.5.352
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy of a forced-air warming system and circulating-water mattress on core temperature and post-anesthesia shivering in elderly patients undergoing total knee arthroplasty under spinal anesthesia

Abstract: BackgroundIn the present study, we compared changes in body temperature and the occurrence of shivering in elderly patients undergoing total knee arthroplasty under spinal anesthesia during warming with either a forced-air warming system or a circulating-water mattress.MethodsForty-six patients were randomly assigned to either the forced-air warming system (N = 23) or circulating-water mattress (N = 23) group. Core temperature was recorded using measurements at the tympanic membrane and rectum. In addition, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
16
0
3
Order By: Relevance
“…However, heater cooler units are also used for extracorporeal membrane M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT oxygenation (ECMO) and similar thermoregulatory devices are also required for circulatingwater mattress to maintain body temperature 50,83 . M. chimaera was detected in 9 of 18 water samples taken from 10 different heater cooler units used for ECMO devices 50 .…”
Section: Implications For Other Thermoregulatory Equipmentmentioning
confidence: 99%
“…However, heater cooler units are also used for extracorporeal membrane M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT oxygenation (ECMO) and similar thermoregulatory devices are also required for circulatingwater mattress to maintain body temperature 50,83 . M. chimaera was detected in 9 of 18 water samples taken from 10 different heater cooler units used for ECMO devices 50 .…”
Section: Implications For Other Thermoregulatory Equipmentmentioning
confidence: 99%
“…In this study, the group that received only a circulating-water mattress to maintain intraoperative temperature was more than twice as likely to experience shivering during the recovery period as the group that received both a mattress and a forced-air warming blanket (Group W = 43.6%, Group F = 20.7%, respectively). It has been demonstrated that regulating body temperature using a forced-air warming device in combination with a circulating-water mattress is more effective in preventing shivering than the use of a mattress alone, as in the findings of Kim et al [ 11 ]. In Group F, the average intraoperative temperature and the temperature at the end of surgery were significantly higher than those of Group W. From these significant differences in temperature, we may infer that the temperature during surgery has had an effect on the occurrence of postanesthetic shivering.…”
Section: Discussionmentioning
confidence: 99%
“…It could also cause heavy financial burden to patients due to prolonged hospital stay (GalvĂŁo et al., 2009). Thus, there has been an increasing interest in the prevention of UIH by means of intraoperative active warming strategies, such as forced‐air warming (FAW) system (Shaw, Steelman, DeBerg, & Schweizer, 2017), prewarming technology before anaesthesia (Poveda, Clark, & GalvĂŁo, 2013) and circulating warming mattresses (Kim et al., 2014). The FAW device, which is comprised of a disposable plastic blanket, joining hose and main machine generating warmed air, has been widely applied in the operating room to surgical patients to prevent UIH for 20 years (Shaw et al., 2017).…”
Section: Introductionmentioning
confidence: 99%